2006
DOI: 10.1124/dmd.105.008342
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 Expression of Cultured Rat Small Hepatocytes after Long-Term Cryopreservation

Abstract: ABSTRACT:Small hepatocytes (SHs) are hepatic progenitor cells that can be cryopreserved for a long time. After thawing, the cells can proliferate and, when treated with Matrigel, they can differentiate into mature hepatocytes (MHs). In this study, we investigated whether cryopreserved SHs could express cytochromes P450 (P450s), whether P450 expression was induced by appropriate inducers, and whether P450 activities were measurable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…As previously reported (Ooe et al, 2006), SH colonies consisting of 30 to 50 cells were observed at day 14 after plating. To collect SHs, the colonies were detached from dishes and immediately replated (subculture) or cryopreserved at Ϫ80°C until use.…”
Section: Methodssupporting
confidence: 61%
See 3 more Smart Citations
“…As previously reported (Ooe et al, 2006), SH colonies consisting of 30 to 50 cells were observed at day 14 after plating. To collect SHs, the colonies were detached from dishes and immediately replated (subculture) or cryopreserved at Ϫ80°C until use.…”
Section: Methodssupporting
confidence: 61%
“…Although, unlike in MHs, PB could not induce RXR␣ expression in the cryo-SHs, these results showed that low expression of CAR might be involved in the poor expression of CYP2B1. Comparing the previous (Miyamoto et al, 2005;Ooe et al, 2006) and present experiments, the difference of the experimental procedure was whether cells were cryopreserved. Thus, we compared the expression of major nuclear receptors involved in the regulation of P450 expression between sub-SHs and cryo-SHs.…”
Section: Cyp2b1 Expression In Ratmentioning
confidence: 99%
See 2 more Smart Citations
“…Manipulation of the growth and maturation of SHs is easy, and they can be cryopreserved 17 . Cryopreserved SHs can maintain the abilities of growth and maturation 18 . Maturated SHs in serum-free culture can be used for studies of hepatic drug metabolism, liver diseases and regenerative medicine.…”
Section: Anticipated Resultsmentioning
confidence: 99%